Strategic industry-university partnerships : success-factors from innovative companies - Frlund, Lars; Riedel, Max F.; Schwab, Klaus (Academic Press, an imprint of Elsevier, 2018)
Strategic Industry-University Partnerships: Success-Factors from Innovative Companies unveils insights of experts from leading companies on managing partnerships with universities. Industry-university partnerships have proved vital to innovation, and although these partnerships can be challenging, careful choices and wise management around five success-factors leads to a systematic approach that unlocks value for both parties. University assessments of these partnerships have been widely described, but industry perspectives are less well understood. This volume captures observations of leading international corporations without omitting university views. It can serve all partners in alliances as a guide to strengthening their organizations. Unveils insights of experts from BMW, DuPont, Ferrovial, IBM, Novo Nordisk, Rolls-Royce, Schlumberger, and SiemensPresents the key challenges of university-industry collaboration and how world-leading companies tackle them.